El CIAT y la agroindustria de la yuca seca en Colombia - Ospina Patiño, Bernardo (International Center for Tropical Agriculture, 1985)
The participation of CIAT in the agroindustrialization of dried cassava in Colombia is briefly indicated. Main area of influence has been on the Atlantic Coast, where an integrated approach to production, processing, and marketing has been employed. The project consists of 3 phases: (1) exptl. phase in which a natural drying plant was built with the collaboration of a group of farmers, data was obtained on cassava drying under prevailing climatic conditions, and the acceptability of the product by the animal feed industry was determined; (2) semicommercial phase in which the operational scale was increased and the economic feasibility of repeating the process in other cassava producing areas was demonstrated; (3) commercial phase in which drying plants were built in different areas of the Atlantic Coast. In 1985, 20 farmer groups were involved in these activities, with a total installed capacity of 20,000 m(2) and a production of approx. 5000 t dried cassava. (CIAT).